Participación y analogía en la fundamentación del derecho según Santo Tomás de Aquino - Herrera, Daniel Alejandro (2004)
Fil: Herrera, Daniel Alejandro. Pontificia Universidad Católica Argentina. Facultad de Derecho; Argentina